"Are you eating healthy?" Nutrition discourse in Midwestern clinics for the underserved. Issue 10 (October 2016) - Curtis, Stephanie M.; Willis, Mary S.
Highlights: Nutrition education provided during medical visits is limited in content. Few patients ask about nutrition in connection with their obesity-related disease. Nutrition students may provide comprehensive education in clinic settings. On-site nutrition education can vastly improve a patient's morbidity related to diet. Abstract: Objective: To investigate nutrition information provided and exchanged between patients and health providers in Midwestern clinics for underserved populations. Methods: Forty-six clinic visits were observed to determine content and direction of nutrition information. In-depth data were collected with clinicians and clinic administrators regarding nutrition education provided to patients. Results: All patients were diagnosed with multiple obesity-related morbidities. Although women more often posed nutrition questions, few patients asked about dietary intake. Two-thirds of healthcare professionals initiated discussion about dietary intake; however, nutrition education was not provided regardless of clinician's profession. Conclusions: Patients did not appear to link morbidity with diet. Providers did not share comprehensive nutrition knowledge during clinic visits. Dietitians, who specialize in nutrition education, rarely had access to patients. Implications: Nutrition education during clinic visits is essential for reducing obesity rates. Nutrition students need clinic experience and could provide important patient education at low cost.